PERKEMBANGAN AKHIR MASA ANAK-ANAK - Amelia Rahmi; Laila Sari; Dwi Putri Lestari (CV. ALIM'SPUBLISHING, 2024)
Abstract. Children's development is usually accompanied by growth so it is more optimal and depends on a person's biological potential. This potential is the result of the interaction of various interrelated factors, namely genetic factors, bio-physical-psycho-social environment and behavior. The unique process and different end results give each child its own characteristics. This research uses a critical review method by reading various books, journals, or other publications related to the research topic discussed by comparing research methods, processing methods, and the results obtained from each article. The research results show that language development in late childhood can be seen from speech progress such as increasing vocabulary, forming sentences and pronunciation. In late childhood, language development reaches a higher level. Children are able to use more complex sentences. Emotional development in late childhood involves various changes and existence caused by learning experiences and self-understanding. Social development occurs quickly, and children begin to learn to adapt to their surroundings. Social development in children requires the role of parents, educators (teachers) and the environment in synergy to develop social aspects in children so that they are able to socialize with the surrounding environment.